Effect of ambient temperature and thyroid hormones on food intake by pigs - Macari, Marcos [UNESP]; Zuim, S. M F; Secato, E. R.; Guerreiro, J. R. (Elsevier, 1986)
Food intake and plasma thyroid hormone levels (T4 and T3) were higher in pigs acclimated to cold (12°) than hot (32°) environments. The exposure of cold pigs to hot ambient temperature decreased food intake and plasma T4 and T3, whereas for hot acclimated animals the change in ambient temperature (from 32 to 12° C) increased food intake and plasma thyroid hormone levels, but the new steady state level of food intake was reached only after 96 hr of temperature transfer despite the rapid change in plasma levels of thyroid hormones. Cold-acclimated pigs, when transferred to a hot environment after thyroidectomy, also reduced food intake, but hot pigs shifted to cold ambient temperature after thyroidectomy did not significantly increase food ingestion. The results of this experiment suggest that food intake adjustment depends on the previous living temperature and that thyroid hormones seem to play an important role in increasing the metabolically active mass that probably sustains the new steady state level of food intake, particularly in a cold environment.
Keywords: thyroid hormone; liothyronine; thyroxine; animal experiment; endocrine system; environmental temperature; food intake; nonhuman; priority journal; swine; acclimatization; animal; blood; cold; eating; female; heat; male; physiology; temperature; Acclimatization; Animal; Cold; Eating; Female; Heat; Male; Support, Non-U.S. Gov't; Swine; Temperature; Thyroid Hormones; Thyroxine; Triiodothyronine